EFL Learners’ Language Learning Strategies: Field Specialization and Gender - Melvina, Melvina; Lengkanawati, Nenden Sri; Wirza, Yanty (UPI Press, 2020)
Learning strategies are considered capable of greatly helping learners improve their proficiency in English and assist them to be more independent. The purpose of the study is to investigate language learning strategies used by secondary school students in Indonesia related to their field of specialization and gender. One hundred and eighty-six eleventh grade students from one of senior high schools in Pekanbaru, Indonesia participated in the survey. This was conducted using the Strategy Inventory for Language Learning (SILL) adopted from (Oxford, 1990) and the Strategy Questionnaire (SQ) adopted from Embi (2000). The collected data were analyzed using descriptive statistics and an independent sample t-test. The findings show that the most frequently used strategy is metacognitive and affective, followed by cognitive and compensation strategies. The least frequently used strategies are social and memory strategies. Besides, it was also found that there were significant differences in the use of strategies between natural and social science students, and there were no significant differences between the two groups of students based on their gender. The study implies that students are aware of language learning strategies, however students still need to be trained to be a successful language learner.